Management of Women with Surgically Staged 1 Uterine Papillary Serous Cancer - Elit, Laurie (International Scholarly Research Network, 2011)
Objective. To review the management and outcomes of women with surgically staged 1 UPSC. Methods. We report on a case series from 2008–2010 from Hamilton Canada. We summarize the data from a literature search on surgically staged 1 UPSC. Results. There is a group women with Stage 1A UPSC with no residual disease at time of surgery who do not require adjuvant therapy. Vault recurrences appear to be lower in women who received adjuvant vault radiation. Chemotherapy appears to confer longer survival for those women with Stage 1B or 1C disease compared of those observed or who had radiation alone. Conclusion. Adjuvant therapy appears to confer benefit in certain groups of women with stage 1 UPSC. A randomized controlled study would clarify the degree of benefit.